ANALISIS KUALITAS PRODUK HARGA DAN CITRA MEREK TERHADAP KEPUASAN PELANGGAN PADA PRODUK SAMSUNG GALAXY SERI A - Emmanuel Adhiseno Wahyukusumo (2023)
In the era of globalization all fields in human life are always developing, one of the most rapid developments is in the field of technology, this development creates a tool to help humans to communicate with one another without space and time limitations, this tool is a smartphone. Smartphones themselves are also experiencing changes starting from form, features, capabilities, to functionality. One of the biggest smartphone manufacturers in the world is Samsung. This brand has a great reputation among the public because it often creates quality, affordable and varied products. The purpose of this research was to analyze product quality, price and brand image on customer satisfaction on Samsung Galaxy A series products. The research approach was carried out using quantitative methods and the data was collected through questionnaires distributed to 100 respondents who have Samsung Galaxy A series products. Data collection was carried out using Google Forms with purposive sampling. The analysis carried out in this study uses the SmartPLS version 4.0 application and the three-box method. The results showed that product quality had a positive and significant influence on customer satisfaction, price had a positive and significant effect on customer satisfaction, and brand image had a positive and significant effect on customer satisfaction.